2019
DOI: 10.1002/cta.2603
|View full text |Cite
|
Sign up to set email alerts
|

Packet‐based feedback control of electrical drive and its application to trajectory tracking of manipulator

Abstract: Summary In systems disconnected from the external grid, such as mobile robots and vehicles, the effective use of renewables and energy harvesting techniques helps a longer operation with less weight and space for batteries. Power packet dispatching system is a promising measure to manage the complex power flow created by such distributed power sources of various profiles. In the system, power is transferred as a pulse, and information tag is attached to the pulse power in voltage waveforms. The physical integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The rule of packetization was proposed in [ 9 ] based on the optimal dynamic quantizers for discrete-valued input control [ 17 , 18 ]. The rule has already been verified on motor drive in a robot arm with a feedback loop [ 19 , 20 ].…”
Section: The Logic Operation Of Electric Powermentioning
confidence: 99%
“…The rule of packetization was proposed in [ 9 ] based on the optimal dynamic quantizers for discrete-valued input control [ 17 , 18 ]. The rule has already been verified on motor drive in a robot arm with a feedback loop [ 19 , 20 ].…”
Section: The Logic Operation Of Electric Powermentioning
confidence: 99%
“…In [6], advantages of the power packet routing for system control are described in detail. As an application of the power packet networks, the trajectory control of a robot arm was realized in [7] by power packets. Reference [7] showed that the motor could be controlled without the control line by transmitting power packets directly to the motor while maintaining correct timing.…”
Section: Power Packet Dispatching Systemmentioning
confidence: 99%
“…As an application of the power packet networks, the trajectory control of a robot arm was realized in [7] by power packets. Reference [7] showed that the motor could be controlled without the control line by transmitting power packets directly to the motor while maintaining correct timing. Therefore, this technology has much potential for implemention in closed systems such as aircrafts, cars, and robots.…”
Section: Power Packet Dispatching Systemmentioning
confidence: 99%
“…When the transient response of power transmission is negligible, the assumption is acceptable. Preceding experimental studies have developed power packet routers (routers) and verified the power packet transmission [2,8,9,10,11]. Routers have capacitors as storage and generate power packets with the stored electric energy.…”
Section: Introductionmentioning
confidence: 99%